Last Ball. Public Policy and Social Practice in the National Casinos around the 1960s (Argentina, 1955-1970) - Pedetta, Marcelo (Universidad Nacional de Mar del Plata. Facultad de Arquitectura, Urbanismo y Diseño, 2019)
The following paper continues the previous research about the processes of nationalization of gambling halls in Argentina (provincialization in the 1930s, nationalization in the 40's). For this, it analyzes what happened with the Casinos between the 1950s and 1970s. We believe that these years belong to the brightest period of the national casinos, essential in the configuration of tourist destinations, both for those that were already consolidated, as well as for the ones that on those years aspired to become an option. This situation became especially visible in the Mar del Plata Central Casino, which on summer nights hosted up to twenty-five thousand people.However, in the second half of the ‘60s, under the dictatorship commanded by J.C. Onganía, a series of adjustment policies were implemented around the “Lotería de Beneficencia Nacional y Casinos”. The arrival of a different time can be noticed, shaped by the end of the “golden years” of the casinos in the Argentina. ark:/s22508112/1nyrkkx2p